Relationship between BDNF content in cord blood and early neurobehavior in newborns with subclinical hypothyroidism during pregnancy: a preliminary study - Hui Xu; Ya-Nan Du; Shuai Yang; Yu-Wen Guo (Frontiers in Neurology)
ObjectivesResearch on neurobehavioral abnormalities in neonates of mothers with subclinical hypothyroidism (SCH) is limited. The link between umbilical cord blood brain-derived neurotrophic factor (BDNF) levels and neurobehavioral outcomes in neonates has not been explored. This study investigates the correlation between alterations in umbilical cord blood BDNF levels and early neurobehavioral abnormalities in neonates born to pregnant women with SCH.MethodsThis study recruited 72 pregnant women with SCH and 76 healthy controls (HC). The study collected general information for all subjects, including body mass index, parity, thyroid function assessed during early to late pregnancy, and neonatal birth weight. Neonatal behavioral and neural abilities were evaluated using the Neonatal Behavioral Neurological Assessment (NBNA). BDNF levels in umbilical cord blood were measured using the Enzyme-Linked Immunosorbent Assay method.ResultsThe results indicated that neonates with SCH during pregnancy had lower total NBNA scores, behavioral ability, passive muscle tone, active muscle tone, primitive reflexes, general assessment, and lower levels of cord blood BDNF compared to healthy controls. The cord blood BDNF of newborns with SCH during pregnancy was positively correlated with total NBNA score, behavioral ability, active muscle tone, and general assessment. Moreover, multiple linear regression analysis demonstrated an association between cord blood BDNF levels in pregnant patients with SCH and multiple measures of newborn health, including total NBNA score, behavioral ability, active muscle tone, and general assessment.ConclusionInfants born to pregnant women with SCH exhibit reduced behavioral and neural abilities linked to BDNF levels in umbilical cord blood.